Comparative anatomy of the skull of adult domestic cat and Indian leopard - KALITA, A; SARMA, M; ROYCHOUDHURY, P; BAISHYA, G (The Indian Journal of Animal Sciences, 2014)
The present study was made on adult skulls of domestic cats (n-6) and Indian leopards (n-6) for their gross anatomical comparison. The temporal line in leopard was curved out from the external sagittal crest to the zygomatic process which was parasagitally placed in domestic cat. The zygomatic process was comparatively pointed. the frontal and transverse palatine sutures were zigzag, and the nasal bones were shorter and wider in leopard. The external occipital protuberance and interparietal bones were also relatively well developed in leopard. However, the occipital condyles were obliquely placed and the jugular processes were well developed and pointed in the domestic cat. The basioccipital bone was comparatively shorter but wider in leopard. Further, the palatine region of leopard was wider and concave while it was elongated and flattened in domestic cat.